2019
DOI: 10.1101/842567
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex differences in Variability of Brain Structure Across the Lifespan

Abstract: Several brain disorders exhibit sex differences in onset, presentation, and prevalence.Increased understanding of the neurobiology of sex-based differences across the lifespan can provide insight into potential disease risk and protective mechanisms. We focused on sex-related differences in variability, which may be indicative of both disease vulnerability and resilience. In n=3,069 participants, from 8-95 years of age, we first analyzed the variance ratio in females vs. males of cortical surface area and glob… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 66 publications
(34 reference statements)
6
13
0
Order By: Relevance
“…Further analysis of our results revealed that the performance of our model depends on subjects’ age and sex. From the sex-based assessments, we observed in most cases (71%) the model performed better in males corroborating the previous studies’ findings, which showed that males’ brain networks have larger variability (i.e., more distinct patterns) than females’ [51,52]. Especially for the first time, we showed functional activity in the SPL network varies more within males than females.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Further analysis of our results revealed that the performance of our model depends on subjects’ age and sex. From the sex-based assessments, we observed in most cases (71%) the model performed better in males corroborating the previous studies’ findings, which showed that males’ brain networks have larger variability (i.e., more distinct patterns) than females’ [51,52]. Especially for the first time, we showed functional activity in the SPL network varies more within males than females.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that male functional networks have more uniquely identifying individual patterns, especially in the cerebellar domain, compared to females. This finding is consistent with studies of brain structure that maintain males’ brains have more variability than females [51,52]. Indeed, higher variability in brain structure is conducive to the existence of more distinct patterns in males that help characterize male subjects’ identities more accurately.…”
Section: Methodssupporting
confidence: 90%
“…In this study, we analyzed a large lifespan sample of neuroimaging data from 16,683 participants spanning nine decades of life starting at birth. Results confirmed the hypothesis of greater male variability in brain structure (Forde et al 2019;Ritchie et al 2018;Wierenga et al 2017;. Variance differences were more pronounced for subcortical volumes and regional cortical surface area than for regional cortical thickness.…”
Section: Discussionsupporting
confidence: 78%
“…body weight and height, blood parameters) already detectable at birth. Recent studies suggest greater male variability also in brain structure and its development (Forde et al 2019;Ritchie et al 2018; Wierenga et al 2017;, but studies with larger samples that cover both early childhood and old age are critically needed. Specifically, we do not know when sex differences in variability in brain structure emerge and whether they change with development and throughout life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation